The impact of transference of learning by using ball holder devise in beating fast and beating fronting skills in volleyball - Mohammed, Zana (Journal of Physical Education, 2016)
The research aims to the following: 1. To identify the impact of the transference of learning using the ball holder for the experimental group in beating fast and beating fronting skills in volleyball. 2. To identify the impact of the transfer of learning in beating fast and beating fronting skills in volleyball in the controlling group. The research methodology and procedures were done by using the experimental approach because of its suitability with the research issue. Twenty students of the second stage of school of physical education were chosen randomly to participate in this study. The outcomes of the study were: 1. The experimental group which has been given the transference of learning with the ball holder attained a positive transmission in both beating fast and beating fronting skills. 2. The controlling group which has been given the transference of learning attained a positive transmission in both beating fast and beating fronting skills. 3. The experimental group which has been given the transference of learning with the ball holder had more positive transmission than the controlling group in both beating fast and beating fronting skills